2017
DOI: 10.1111/eth.12625
|View full text |Cite
|
Sign up to set email alerts
|

Condition explains individual variation in mobbing behavior

Abstract: During mobbing, individuals approach predators with the apparent aim of reducing the risk of predation. The intensity of mobbing may depend on the costs and benefits of this behavior, which likely vary among individuals and between different social contexts. We studied whether Dark‐eyed junco male mobbing behavior is related to social environment, individual condition, and age during experimentally induced mobbing events. Based on risk‐taking theory, we predicted that individuals with high residual reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(81 reference statements)
0
6
0
Order By: Relevance
“…Mass has been associated with egg rejection in interspecific comparisons (Peer & Sealy, 2004), where larger species are more likely to reject parasitic eggs. At an intraspecific level, heavier females may have higher expected future reproductive success (Abolins-Abols & Ketterson, 2017; Blums, Clark, & Mednis, 2002), possibly leading to a reduced sensitivity to parasitic stimuli. More focal experimental work will be needed to assess the mechanisms behind this association.…”
Section: Discussionmentioning
confidence: 99%
“…Mass has been associated with egg rejection in interspecific comparisons (Peer & Sealy, 2004), where larger species are more likely to reject parasitic eggs. At an intraspecific level, heavier females may have higher expected future reproductive success (Abolins-Abols & Ketterson, 2017; Blums, Clark, & Mednis, 2002), possibly leading to a reduced sensitivity to parasitic stimuli. More focal experimental work will be needed to assess the mechanisms behind this association.…”
Section: Discussionmentioning
confidence: 99%
“…However, the principal benefit of mobbing is thought to be predator deterrence, either by intimidating and driving away the predator, or by alerting it that it has been detected and thus reducing the chance of successful attack (Abolins-Abols & Ketterson, 2017;Caro, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we also found that participation in mobbing was more sensitive to the potential costs of participation than the potential benefits of success, as hyenas were most likely to mob in sessions where risk was relatively low regardless of potential resource benefits. Studies of mobbing in other species similarly indicate that mobbing participants are often the group members with the lowest cost-benefit ratios [ 40 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also predicted that hyenas would be more likely to participate when they are in top physical condition (i.e. prime-aged and good nutritional state), such that they can escape from lions more easily and thus bear a lower cost of participation [ 14 , 40 ]. Based on theoretical studies showing the importance of social networks to successful cooperation [ 16 , 17 ], we also predicted that hyenas would be more likely to participate when their social allies or kin are present, as occurs in other socially complex species [ 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%